Prevention and treatment of ischaemic and haemorrhagic stroke in people with diabetes mellitus: a focus on glucose control and comorbidities - Sacco, S; Foschi, M; Ornello, R; De Santis, F; Pofi, R; Romoli, M (Springer, 2024)
Diabetes mellitus is a significant risk factor for both ischaemic and haemorrhagic stroke, affecting up to a third of individuals with cerebrovascular diseases. Beyond being a risk factor for stroke, diabetes and hyperglycaemia have a negative impact on outcomes after ischaemic and haemorrhagic stroke. Hyperglycaemia during the acute ischaemic stroke phase is associated with a higher risk of haemorrhagic transformation and poor functional outcome, with evidence in favour of early intervention to limit and manage severe hyperglycaemia. Similarly, intensive glucose control nested in a broader bundle of care, including blood pressure, coagulation and temperature control, can provide substantial benefit for clinical outcomes after haemorrhagic stroke. As micro- and macrovascular complications are frequent in people with diabetes, cardiovascular prevention strategies also need to consider tailored treatment. In this regard, the broader availability of sodium–glucose cotransporter 2 inhibitors and glucagon-like peptide 1 receptor agonists can allow tailored treatments, particularly for those with heart failure and chronic kidney disease as comorbidities. Here, we review the main concepts of hyperacute stroke management and CVD prevention among people with diabetes, capitalising on results from large studies and RCTs to inform clinicians on preferred treatments. Graphical Abstract: